The Crab-Stuffed Orange - Flögel, Thomas (Petits Propos Culinaires, 1988)
This is the author’s last contribution from Taiwan, as he returns to Germany this summer. He is, however, scouring the libraries in Taipei for a final haul of esoteric information to bring back for us.